Predictive equations over estimating resting metabolic rate in individual with spinal cord injury requiring mechanical ventilation support – A case series. (2nd January 2022) - Wong, Samford; Subong, Paul; Graham, Allison; Wail, Ahmed; Derry, Fadel; Saif, Mofid; Belci, Maurizio
Abstract : Context: The impact of mechanical ventilation on energy expenditure after spinal cord injury (SCI) is sparse. The objective of this case-series is to measure 15-minutes resting metabolic rate (RMR) to determine 24-hours measured-RMR (m-RMR) using QUARK indirect calorimeter (IC) and; compare the m-RMR with estimated RMR (e-RMR) using four commonly used predictive equations (Harris-Benedict, Mifflin St-Jeor, Henry and Schofield). Findings: We measured the RMR of four patients with SCI (one male and three female; mean age: 58.3 years) all with complete tetraplegia (ISNCSCI A) twice in a one-week interval using an IC with two sampling flow settings during a six month period. The median (IQ) of all m-RMRs was 1094 (340.2) kcal/day. The median m-RMR was 40.1% lower than the median calculated with four different e-RMRs using predictive equations. All four predictive equations overestimated RMR in SCI patients requiring mechanical ventilation by 4.1–61.1% (Harris-Benedict: 28.8–60.6%; Mifflin St-Jeor: 6.9–61.1%; Henry: 4.1–58.9% and; Schofield: 6–54.6%). Conclusion/clinical relevance: There is a high variability of e-RMR and m-RMR in patients with SCI who are dependent on mechanical ventilation. The use of predictive equations may lead to over-estimation of energy requirements. To avoid overfeeding we recommended measuring RMR using IC wherever possible. A further study with a larger sample size is needed due to the small number of subjects in our case-series. Development of a validated RMR equation in the SCI population is warranted